The ANALYSIS OF DEIXIS IN THE NOVEL TWELVE YEARS A SLAVE BY SALOMON NORTHU: DEIXIS IN A NOVEL - Esterria Romauli Panjaitan; Yeni Noryatin (STBA JIA Press, 2021)
This study is entitled The Analysis of Deixis in The Novel, Twelve Years A Slave by Salomon Northup. This research activity was carried out from September 2019 to September 2020. Deixis in this research was to describe the relationship between language and contexts in the structure of language itself. The goals of this study are to find out, identify types of deixis, and to analyze the function of each type of deixis found in the novel of Twelve Years a Slave by Salomon Northup. The writer used the theory of Levinson and Jaszczolt. The data collection techniques, are reading and understanding the contents of the novel, searching for data, marking, and putting a check mark, taking data and processing it into a data framework. Qualitative method was used in this study to analyze the data and the method were done by descriptive technique. Obviously, the result of the research can be shown that there are three types of deixis found in the novel, Twelve Years A Slave by Salomon Northup, namely person deixis, spatial deixis and temporal deixis. Person deixis consists of first person, second person and third person. The first person deixis is used to identify the speaker. The second person deixis is used to show the addressee. The third person deixis is used to show the referent not Panjaitan, Ester. Noryatin, Yeni (2020). The Analysis of Deixis in The Novel Twelve Years A slave by Salomon Northup. Jurnal Bahasa Asing. Vol. 1. Desember 2021, pp. 1-14identified neither speaker nor the addressee. The spatial deixis is used to describe a location participant in speech event. Temporal deixis is used to point a certain period of time.Keywords: Deixis, Referent, Novel.